6m-8=2+9m-11

Simple and best practice solution for 6m-8=2+9m-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-8=2+9m-11 equation:


Simplifying
6m + -8 = 2 + 9m + -11

Reorder the terms:
-8 + 6m = 2 + 9m + -11

Reorder the terms:
-8 + 6m = 2 + -11 + 9m

Combine like terms: 2 + -11 = -9
-8 + 6m = -9 + 9m

Solving
-8 + 6m = -9 + 9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9m' to each side of the equation.
-8 + 6m + -9m = -9 + 9m + -9m

Combine like terms: 6m + -9m = -3m
-8 + -3m = -9 + 9m + -9m

Combine like terms: 9m + -9m = 0
-8 + -3m = -9 + 0
-8 + -3m = -9

Add '8' to each side of the equation.
-8 + 8 + -3m = -9 + 8

Combine like terms: -8 + 8 = 0
0 + -3m = -9 + 8
-3m = -9 + 8

Combine like terms: -9 + 8 = -1
-3m = -1

Divide each side by '-3'.
m = 0.3333333333

Simplifying
m = 0.3333333333

See similar equations:

| 2(z-1)=4(z+5)-10 | | 5(y-7)/4=-2y | | 2.4x=-8.4 | | 3x-5x=20 | | 1/4x-5=-25 | | x^(2/3)-2x^(1/3)-8=0 | | 11-6y-19=7y+8-5y | | 6x+2+3x=9x+2 | | 64/5n-8/9=7/15n | | 11y-5y+6=-24-9y | | 6(7x-3)-4=42x-22 | | n^2-4n-35=0 | | 4y+9=-2y-9 | | 11=8x-8 | | W=1925+-550t | | 2/3d+2/3=8/9 | | (a^8b^4)(-a^2b)= | | 6+2y=7y-2.4 | | -2x+8=-100+7x | | F/5-2.2=-2.5 | | 11+-3x=12-20 | | 2x+3(x-9)=2(x+3) | | 4(8x+9)14y=56 | | 1/6+2y=7y-5/12 | | 2-5x=-14x | | 5n-7=5n-10 | | (2x^3z)(81x^4z^2)(5z)(x^6z^3)= | | -34=3d+8/3 | | (2y-7)(2y-7)=12 | | m-14/a=-27 | | 4x+5=3-2x | | 6m=-1/3 |

Equations solver categories